2022
DOI: 10.4103/nah.nah_21_22
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Noise Exposure on Risk of Developing Stress-Related Metabolic Effects: A Systematic Review and Meta-Analysis

Abstract: Background: Exposure to noise can increase biological stress reactions, which may increase adverse health effects, including metabolic disorders; however, the certainty in the association between exposure to noise and metabolic outcomes has not been widely explored. The objective of this review is to evaluate the evidence between noise exposures and metabolic effects. Materials and Methods: A systematic review of English and comparative studies available in PubMed, Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…A 2021 review assessed hypertension in relation to transportation noise and derived pooled estimates stratified by noise source and study type. 48 While the metaanalysis for road traffic noise showed no association between cohort and case-control studies, an increased odds ratio of 9% per 10 dB(A) was seen in crosssectional studies. No associations were observed between The lower effect threshold of road traffic noise, corresponding the level below which no health effects of noise are expected, is presently unknown, and, therefore, numbers are estimated for 4 lower harmful level scenarios.…”
Section: Arterial Hypertensionmentioning
confidence: 92%
See 2 more Smart Citations
“…A 2021 review assessed hypertension in relation to transportation noise and derived pooled estimates stratified by noise source and study type. 48 While the metaanalysis for road traffic noise showed no association between cohort and case-control studies, an increased odds ratio of 9% per 10 dB(A) was seen in crosssectional studies. No associations were observed between The lower effect threshold of road traffic noise, corresponding the level below which no health effects of noise are expected, is presently unknown, and, therefore, numbers are estimated for 4 lower harmful level scenarios.…”
Section: Arterial Hypertensionmentioning
confidence: 92%
“…A 2021 review assessed hypertension in relation to transportation noise and derived pooled estimates stratified by noise source and study type. 48 While the meta-analysis for road traffic noise showed no association between cohort and case-control studies, an increased odds ratio of 9% per 10 dB(A) was seen in cross-sectional studies. No associations were observed between aircraft and railway noise.…”
Section: Epidemiological Evidencementioning
confidence: 93%
See 1 more Smart Citation
“…It has been proposed that this stressor causes changes that could influence pregnancy by increasing stress hormones through the activation of inflammatory pathways by stimulating the sympathetic nervous system. 6 Exposure to environmental noise from factories, trains, and airplanes before conception and during pregnancy has been associated with delayed time to achieve pregnancy. 33 Numerous studies have investigated how noise affects both fetal growth and embryogenic size; however, some studies have shown effects of noise on growth, whereas others have not shown any effects.…”
Section: Effect(s) Of Noise On Embryonic/fetal Growthmentioning
confidence: 99%
“…33 Numerous studies have investigated how noise affects both fetal growth and embryogenic size; however, some studies have shown effects of noise on growth, whereas others have not shown any effects. [6][7][8][9][10][11][12] Currently, the effects, if any, on noise exposure and embryonic/fetal growth remain uncertain.…”
Section: Effect(s) Of Noise On Embryonic/fetal Growthmentioning
confidence: 99%